Panace@. Revista de medicina, lenguaje y traducción, vol. XX, nº 50, 122pp. ISSN 1537-1964. - Torres Ruiz, Rosa (Philologia Hispalensis, 2021)
Reseña de Panace@. Revista de medicina, lenguaje y traducción, vol. XX, nº 50, 122pp. ISSN 1537-1964.